Learning from the lived experiences of graduate student writers - Madden, Shannon, editor; Eodice, Michele, editor; Edwards, Kirsten T., editor; Lockett, Alexandria, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2020)
A resource for understanding and resolving issues graduate students face. Offering diverse approaches, this book bridges the gap between theory and practice through structured examination of graduate students' narratives about their development as writers, as well as researched approaches for enabling these students to cultivate their craft--provided by publisher.
The trauma of graduate education / Beth Godbee -- Incidents in the life of Kirsten T. Edwards / Kirsten T. Edwards Williams -- Voices from the hill / Richard Sévère and Maurice Wilson -- Race, retention, language, and literacy / Wonderful Faison and Willow Treviño -- Paying it forward by looking back / Karen Keaton Jackson, Hope Jackson, Kendra L. Mitchell, Pamela Strong Simmons, Cecilia D. Shelton, and LaKela Atkinson -- Graduate writing in communities / Alexandria Lockett -- Mi testimonio / Amanda E. Cuellar -- "I cut my hand off and gave it to you, and you gave it back with three fingers" / Jasmine Kar Tang and Noro Andriamanalina -- Research writing as an adaptive challenge / Daniel V. Bommarito -- From avoidance to action / Lisa Russell-Pinson and Haadi Jafarian -- Dissertation boot camps / Rachael Cayley -- Not just nuts and bolts / Anne Zanzucchi and Amy Fenstermaker -- Playing with theory in graduate writing groups / Rochelle Rodrigo and Julia Romberger -- Planning, implementing, and evaluating a campus-wide graduate writing initiative at an urban midwestern university / Jennifer Friend, Jennifer Salvo-Eaton, Michelle M. Paquette, and Elizabeth Brown.
Keywords: Academic writing